1997
DOI: 10.1002/(sici)1098-237x(199711)81:6<763::aid-sce11>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Moving from task-oriented to learning-oriented strategies on school excursions to museums

Abstract: Museums are best considered as venues for informal learning and yet the authors' observations were that most school classes that visit museums are restricted and structured, the students not being provided with optimal opportunities to learn in an informal manner. Although research has addressed some features of successful school group visits to museums, such as preparation and orientation, emphasis on first‐hand experience, and use of worksheets, there has been little research on the role of the class teacher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
138
1
36

Year Published

2000
2000
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 230 publications
(179 citation statements)
references
References 22 publications
4
138
1
36
Order By: Relevance
“…The Israeli Ministry of Education acknowledges and supports museum-learning experiences by funding a large number of centers according to their number of student visits and educational programs (Carmeli & Shavit, 2001). Although schools and teachers attribute high value to the museum visit, the international literature indicates that teachers hardly define their goals for the museum visit, they rarely plan or enact previsit activities, and they hardly ever perceive the museum activity as engaging sociocultural learning experience (Cox Petersen et al, 2003;Griffin, 2004;Griffin & Symington, 1997;Kisiel, 2003;Price & Hein, 1991).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…The Israeli Ministry of Education acknowledges and supports museum-learning experiences by funding a large number of centers according to their number of student visits and educational programs (Carmeli & Shavit, 2001). Although schools and teachers attribute high value to the museum visit, the international literature indicates that teachers hardly define their goals for the museum visit, they rarely plan or enact previsit activities, and they hardly ever perceive the museum activity as engaging sociocultural learning experience (Cox Petersen et al, 2003;Griffin, 2004;Griffin & Symington, 1997;Kisiel, 2003;Price & Hein, 1991).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Very little preparation is done for museum excursions, and even then, most of the preparation is technical and focuses on schedules and instructions regarding clothing and food (Griffin & Symington, 1997). Most of the studies that reported about meaningful preparation or follow-up activities described research settings, in which the researchers were involved in preparing the activity with the teachers or the museum staff (Anderson et al, 2000;Gilbert & Priest, 1997;Henriksen & Jorde, 2001).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…The nature of this difference however varies greatly. Some researchers argue that informal learning is almost entirely self guided, with very little structure or direct participation on the part of the teacher (Wells 1999;Griffin and Symington 1997;Gallas, 1994). Others take a more moderate view, arguing that informal learning can be a component of a larger, highly structured learning experience, or a learning experience in and of itself which is fairly structured and teacher guided (Fernandez-Manzanal et al, 1999;Minstrell 1999;Ryder et al, 1998;Jones 1997;Rosebery et al 1992;).…”
Section: Introduction To the Problem And Backgroundmentioning
confidence: 99%
“…It is important to recognize that there is a body of evidence, much of it focusing on school field trips, indicating that school-ISI interactions can indeed support student learning and that certain pedagogical strategies can be used for creating beneficial science learning experiences (see, e.g., Anderson & Lucas, 1997;Bamberger & Tal, 2007;Falk, Martin, & Balling, 1978;Gennaro, 1981;Griffin, 1994;Kubota & Olstad, 1991;Orion, 1993;Rennie & McClafferty, 1995;Storksdieck, Werner, & Kaul, 2005). Several studies suggest, however, that these research efforts are not effectively informing teacher practice within the museum setting (Anderson, Kisiel, & Storksdieck, 2006;DeWitt & Storksdieck, 2008;Griffin & Symington, 1997;Kisiel, 2005Kisiel, , 2007Storksdieck et al, 2005). Furthermore, recent studies suggest that science museum resources are generally underused by the teachers they hope to serve (Bevan, 2007;Finkelstein, 2005;Phillips, Finkelstein, & Wever-Frerichs, 2007) and that external factors such as rising costs and accountability concerns are likely influencing teacher and school participation (Anderson et al, 2006;DeWitt & Storksdieck, 2008).…”
Section: Introduction the Possibilities Of Collaboration Between Schomentioning
confidence: 99%